Igualdad en Rebaja. Reflexiones críticas en torno a la filosofía política de Ronald Dworkin - Gustavo Arosemena (Ius Humani. Jornal do direito, 2016)
The article presents a critique of the egalitarian political philosophy of Ronald Dworkin in light of two alternative conceptions of equality. First, in light of a political conception of equality based on the thoughts of Thomas Hobbes. Afterwards, in light of a “mystical” conception of equality based on the work of authors such as Elizabeth Anscombe and Bernard Williams. It is held that these conceptions of equality are stronger than the one presented by Dworkin and that together they leave little room for the liberal equality that Dworkin prefers. In the end, the article presents reflections on the importance of granting ethics a stronger role in grounding normative theories than the one given by Dworkin. Dworkin aims to create a relation of reciprocity and mutual accommodation between ethics and morality. In reality, ethics has primacy and what is to be sought is not to accommodate these two ideas but to fully derive morality from ethics.